Penggunaan Kitosan Sebagai Bahan Pengawet Untuk Mempertahankan Mutu Ikan Selar Bentong (Selar crumenophthalmus) Segar Selama Penyimpanan Pada Suhu Ruang - Irianis Lucky Latupeirissa (AGRICOLA, 2015)
This study aims to find out the change of the quality of fresh selar bentong fish (Selar crumenophthalmus) in storage with room temperature. The fish is previously preserved by using chitosan.The research used the factorial complete random design with two factors: the way in treating the fish (cleaned or uncleaned) and the chitosan concentration. The data were analysed by using the analysis of variance, continued with the Tukey's test and t-test.The results reveal that chitosan gives a significant effect in all parameters that have been analysed. Cleaning treatment with a chitosan concentration of 3% gives a better effect on the chemical value of fresh selar bentong fish from the 1st until the 3rd day. Cleaned and uncleaned selar bentong fish that has been dipped in chitosan solution from the 1st day does not fulfil the organoleptic requirement based on the Indonesian National Standard (SNI 01 2354.2 2006) for fresh fish which is greater or equal to 7(7). The result of TPC calculation reveals that cleaned selar bentong fish that has been dipped into chitosan solution of 3% gives good result, based on the inhibition of TPC'S growth. The use of chitosan concentration of 3% can be further applied because the concentration of 3% can decrease the number of bacteria and the chemical value, and keep the organoleptic condition of selar bentong fish. This is better than the chitosan concentration of 1% and 2%.